Assessing Biology Education Students’ Self-Efficacy in Data Literacy: An Analysis of Their Confidence in Understanding Data - Siswandari, Puti; Puspitaningrum, Hardini; Solihat, Rini (Universitas Sultan Ageng Tirtayasa, 2025)
Data literacy is an essential aspect in science and education, yet its integration in biology education remains underexplored. Competence in data literacy is essential for biology education students to conduct learning evaluation analyses that increase student learning performance. Grounded in Bandura’s social cognitive theory, this study investigates biology education undergraduates’ self-efficacy in data literacy during a statistics course. A convenience sample of 70 students completed a questionnaire assessing confidence (7 items), experience (4 items), and attitude (4 items) of data on a 5-point Likert scale. Additionally, students completed a data interpretation test (with biology-based data scenarios), rated their confidence on a 4-point Likert scale, and provided reasoning. Result revealed high levels of self-efficacy across all domains, consistent confidence during data interpretation tasks, and positive attitudes towards learning with data. The study contributes conceptually by linking perceived confidence and performance-based evidence of data literacy, highlighting implications for improving quantitative reasoning in biology education